J-shape relation of blood pressure reduction and outcome in acute intracerebral hemorrhage: A pooled analysis of INTERACT2 and ATACH-II individual participant data - Wang, Xia; Di Tanna, Gian Luca; Moullaali, Tom J; Martin, Renee' H; Shipes, Virginia B; Robinson, Thompson G; Chalmers, John; Suarez, Jose I; Qureshi, Adnan I; Palesch, Yuko Y; Anderson, Craig S (International journal of stroke, 2022)
The aim of this study was to better define the shape of association between the degree ("magnitude") of early (< 1 h) reduction in systolic blood pressure (SBP) and outcomes in patients with acute intracerebral hemorrhage (ICH) through pooled analysis of the second Intensive Blood Pressure Reduction in Acute Cerebral Hemorrhage Trial (INTERACT2) and second Antihypertensive Treatment of Acute Cerebral Hemorrhage (ATACH-II) datasets. Association of the continuous magnitude of SBP reduction described using cubic splines and an ordinal measure of the functional outcome on the modified Rankin scale (mRS) scores at 90 days were analyzed in generalized linear mixed models. Models were adjusted for achieved (mean) and variability (standard deviation, SD) of SBP between 1 and 24 h, various baseline covariates, and trial as a random effect. Among 3796 patients (mean age 63.1 (SD = 13.0) years; female 37.4%), with a mean magnitude (< 1 h) of SBP reduction of 28.5 (22.8) mmHg, those with larger magnitude were more often non-Asian and female, had higher baseline SBP, received multiple blood pressure (BP) lowering agents, and achieved lower SBP levels in 1-24 h. Compared to those patients with no SBP reduction within 1 h (reference), the adjusted odds of unfavorable functional outcome, according to a shift in mRS scores, were lower for SBP reductions up to 60 mmHg with an inflection point between 32 and 46 mmHg, but significantly higher for SBP reductions > 70 mmHg. Similar J-shape associations were evident across various time epochs across 24 h and consistent according to baseline hematoma volume and SBP and history of hypertension. A moderate degree of rapid SBP lowering is associated with improved functional outcome after ICH, but large SBP reductions over 1 h (e.g. from > 200 to target < 140 mmHg) were associated with reduction, or reversal, of any such benefit.